Liquid-liquid equilibrium of the 1-butyl-3-methylimidazolium-based ionic liquids + sodium citrate + water systems at 298.15 K - Gallo-García, Luis A.; Freire, Nian V. [UNESP]; Guimarães, Daniela H.P.; Biaggio, Francisco C.; Arce, Pedro F. (Elsevier, 2024)
Liquid-liquid extraction has long been the preferred option for process engineers to develop separation processes and it is used to separate and purify various biological products, metallic ions, colorants, pharmaceutical molecules, and small organic species. Ionic liquids (ILs) are special ecological solvents that can be used as possible substitutes for traditional organic solvents used for extraction and separation processes, becoming them more sustainable and safer. In combination with salts or inorganic polymers, they can form a liquid system of two phases, advantageous due to its wide polarity and viscosity. In this scenario, liquid–liquid equilibrium (LLE) data and phase diagrams for new aqueous two-phase systems containing ionic liquid ([BMIM][OH], [BMIM][Cl], [BMIM][Br]) (1) + sodium citrate (2) + water (3) were determined experimentally at 298.15 K. The ionic liquids were synthesized and characterized in the first part of the study. COSMO-RS was used as a tool to calculate polarity graphs of study molecules. In the second part, liquid–liquid equilibrium was studied using experimental measurements of the binodal curve and tie-lines, testing the quality of experimental data by mass balance, thermodynamic modeling using the NRTL model to correlate liquid–liquid equilibrium data and to do their phase stability. The accuracy of the model data results was verified by Gibbs energy topological mixing surface analysis and σ profiles. The experimental results indicated that the studied systems had type I liquid–liquid phase behavior. It was demonstrated that the ionic liquid [BMIM][OH] demonstrated better behavior to form Aqueous Two-Phase Systems mixed with sodium citrate and water. The results obtained by the thermodynamic modeling and stability with NRTL model weren't satisfactory, because, besides the low deviations for the liquid phases compositions, the majority of calculated tie-lines was not tangent with the Gibbs surface, showing the limitations of the model for systems with electrolytes.
Keywords: Aqueous two-phase system; Ionic liquid; Liquid–liquid equilibrium; NRTL model